Breaking the Thumb Sucking Habit: When Compliance Is Essential - Orlando Tanaka; Wagner Oliveira; Melissa Galarza; Vanessa Aoki; Bruno Bertaiolli (Hindawi Limited, 2016)
The anterior open bite (AOB) and posterior cross bite are the most frequent malocclusions associated with prolonged sucking habits. This clinical case illustrates and discusses the use of a Haas-type palatal expander for stopping a thumb sucking habit. The improvement in closing the open bite with discontinuation of the habit was observed. But with the return of the habit and lack of cooperation, the relapse of anterior open bite occurred. Therefore, different approaches are necessary. The need of a multidisciplinary approach, consent, and cooperation are keys to a good prognosis.